NAD+ in COVID-19 and viral infections. Issue 4 (April 2022) - Zheng, Minyan; Schultz, Michael B.; Sinclair, David A.
Abstract : NAD +, as an emerging regulator of immune responses during viral infections, may be a promising therapeutic target for coronavirus disease 2019 (COVID-19). In this Opinion, we suggest that interventions that boost NAD + levels might promote antiviral defense and suppress uncontrolled inflammation. We discuss the association between low NAD + concentrations and risk factors for poor COVID-19 outcomes, including aging and common comorbidities. Mechanistically, we outline how viral infections can further deplete NAD + and its roles in antiviral defense and inflammation. We also describe how coronaviruses can subvert NAD + -mediated actions via genes that remove NAD + modifications and activate the NOD-, LRR-, and pyrin domain-containing protein 3 (NLRP3) inflammasome. Finally, we explore ongoing approaches to boost NAD + concentrations in the clinic to putatively increase antiviral responses while curtailing hyperinflammation. Highlights: NAD + can exert both antiviral and anti-inflammatory effects in mice and humans, which might be beneficial during coronavirus disease 2019 (COVID-19) infections. Compared with healthy individuals, NAD + concentrations in tissues and organs are lower in older individuals and in patients with diseases associated with severe COVID-19 symptoms, including diabetes and cardiovascular disease. Viral infections, including coronavirus infections, have been reported to further deplete cellular NAD + stores. Many NAD + -dependent enzymes, including members of the sirtuin and poly-ADP-ribose polymerase (PARP) families, display potent antiviral activities. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and a variety of viruses possess ADP-ribosyl hydrolase activity, which counteracts the activity of PARPs. Viruses such as SARS-CoV-2 can hyperactivate the immune system by activating nuclear factor kappa B (NF-κB) and the NOD-, LRR-, and pyrin domain-containing protein 3 (NLRP3) inflammasome, potentially leading to deadly cytokine storms. NAD + -boosting compounds may counteract these processes. Several NAD + -boosting compounds and molecules that target NAD + -producing or -consuming enzymes are in clinical development as putative anti-inflammatory or antiviral drugs.